Implications of the circular RNAs in localized prostate cancer - Nigam, Shivansh; Manzar, Nishat; Ateeq, Bushra (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
Stochastic and contingent events in molecular biology tune the advent of new molecular entities, most recent being the circular RNAs (circRNAs) which bestowed new avenues in cancer research. The circRNAs are stable, single-stranded covalently closed transcripts resulting from the back-splicing events of RNA (1). circRNAs are present in the plasma, cell-free saliva and urine of cancer patients and healthy individuals, either in the free forms or bound to the proteins or associated with exosomes highlighting their importance as non-invasive biomarkers (2).